Ecological Fiscal Transfers in Europe: Evidence-based design options of a transnational scheme - N. Droste; I. Ring; R. Santos; M. Kettunen (Helmholtz-Zentrum für Umweltforschung (UFZ), 2016)
Ecological Fiscal Transfers (EFT) have recently gained attention as a promising instrument to provide incentives for nature conservation addressing public authorities. In parallel, both the EU and different European countries are exploring new mechanisms to mobilise funding to support biodiversity conservation. So far, existing EFT mechanisms in Europe have been implemented at the national level in Portugal and, to some extent, in France while in Brazil EFT schemes exist between the state and local level. In this paper we develop a proposal for an EFT design within the supranational context of the EU and assess its potential effects with evidence-based estimates. To provide such a knowledge base for a potential supranational EU-EFT implementation, we i) provide a theoretical underpinning, and an analytical synthesis of the current experiences both with the uptake of EFT and the implementation of EU's nature conservation legislation (i.e. the Habitats and Bird Directives), ii) propose a model for an EFT implementation within the existing EU funding framework for N2k financing which is built upon both quantitative and qualitative conservation indicators, iii) compute fiscal effects of our suggested model and analyse how the resulting payments would be (spatially) distributed among European regions, and iv) discuss the model outcomes in terms of ecological effectiveness, distributive effects, and cost-efficiency. Thereby we aim at stimulating a debate about how to better integrate ecological public functions within multi-level and supra-national governance structures.
Keywords: C31; H77; H87; P48; R12; Q57; 330; Ecological Fiscal Transfers; European Union; Natura 2000 network; policy advice; spatial econometrics